Pandemic Depression: COVID-19 and the Mental Health of the Self-Employed - Marco Caliendo; Daniel Graeber; Alexander S. Kritikos; Johannes Seebauer (Institute of Labor Economics (IZA), 2022)
We investigate the effect of the COVID-19 pandemic on self-employed people\~AƒÂ\~Aâ exteurošÂ¬\~Aâ exteurožÂs mental health. Using representative longitudinal survey data from Germany, we reveal differential effects by gender: whereas self-employed women experienced a substantial deterioration in their mental health, self-employed men displayed no significant changes up to early 2021. Financial losses are important in explaining these differences. In addition, we find larger mental health responses among self-employed women who were directly affected by government-imposed restrictions and bore an increased childcare burden due to school and daycare closures. We also find that self-employed individuals who are more resilient coped better with the crisis.
Keywords: L26; D31; I14; I18; J16; 330; representative longitudinal survey data; self-employment; gender; mental health; COVID-19; PHQ-4 score; resilience